Capsaicin: A Potential Therapy Adjuvant for Intestinal Bowel Disease - Elandia, A dos Santos; Jacqueline, I Alvarez-Leite (Journal of Digestive Disorders And Diagnosis, 2019)
Most of the patients with inflammatory bowel disease avoid pepper or spicy food, alleging that this condiment causes anal sensation of burning and accelerates intestinal movements. Capsaicin is the main bioactive component of peppers responsible for the pungent flavor that characterizes red peppers. Capsaicin has been related to several biological effects, including decreased body fat, antianti-inflammatory, anticarcinogenic, antioxidant activites and modulator of intestinal motility. These actions mostly are due to its role as an agonist of the transient receptor potential vanilloid 1 (TRPV1), expressed in the mesenteric nervous system and epithelial cells of the colon. Nonetheless, the anti-inflammatory action of capsaicin is also related to its role in activating the peroxisomal proliferator-activated receptor gamma (PPAR-γ). Topical capsaicin formulations are already used for pain management, but oral administration of capsaicin is rare. Here, we discuss the main actions of capsaicin that could interfere with the symptoms and severity of IBD. Although animal experiments suggest a beneficial effect of capsaicin on colitis, clinical studies exploring the potential analgesic and anti-inflammatory of capsaicin on Crohn or Ulcerative Colitis are scarce. We concluded that there is no evidence that capsaicin aggravates IBD symptoms or severity. On the opposite, experimental studies suggest that capsaicin could reduce intestinal inflammation by a mechanism that could involve not only the TRPV1 receptor but also PPAR γ. However, clinical studies are still scarce, and data regarding capsaicin concentrations, routes of administration, and long-term side-effects need to be better understood before its use.
Keywords: Capsaicin; Ulcerative Colitis; Crohn disease; inflammatory bowel disease; inflammation; TRPV1; PPAR-γ